Selknamella: a new agglutinated foraminiferal genus from the early Eocene southern high latitudes - Malumian, Norberto (2014)
A new, unusual agglutinated foraminifera, Selknamella basketi n. gen., n. sp. is described from the Fuegian lower Eocene, Magallanes Basin, southernmost South America. It has a morphology and paleohabitat similar to those of the subfamily Remaneicinae Loeblich and Tappan, 1964, particularly to the Holocene genera Bruneica Brönnimann, Keij and Zaninetti, 1983, and Remaneica Rhumbler, 1938: It has a low trochospirally coiled to patelliform small test; the first two or three embryonic chambers are globular and undivided; following chambers are semilunate-shaped from spiral view and mushroom-shaped from umbilical view, and subdivided by radial secondary septula. Selknamella n. gen. differs from all the organically-cemented Remaneicinae by the perforate rigid wall, completely calcareous in the initial chambers to very finely agglutinated in the last whorls. The new genus is the only case of calcareous cemented agglutinated foraminifera in the Cretaceous and Cenozoic of the Magallanes Basin, and is restricted to the early Eocene, coincident with the warmest time in the high southern latitudes.